Unintended pregnancy and gender inequality worldwide: an ecological analysis - Gilda Sedgh; Jonathan Marc Bearak (BMJ Global Health)
Unintended pregnancy compromises many women’s and girls’ ability to pursue the lives that they want. The conditional unintended pregnancy rate (CUPR) is a measure of unintended pregnancy among women who wish to avoid getting pregnant. Using the CUPR, we explore the relationship between gender inequality and unintended pregnancy across 132 countries. We used gender inequality indicators from the UNDP Human Development Report and estimates of the incidence of unintended pregnancy published by the Guttmacher Institute and WHO. We regressed the CUPR on several measures of gender inequality using least squares with a percentile bootstrap to account for sampling error and the additional uncertainty in the model-based unintended pregnancy estimates. We find that unintended pregnancy is positively correlated with multiple composite measures of gender inequality, even after controlling for countries’ levels of economic development. Of the components of gender inequality, gender disparities in educational attainment were most strongly correlated with unintended pregnancy in multivariable regressions. We also find that female educational attainment is a stronger predictor of the CUPR than male educational attainment. Analyses with the standard unintended pregnancy rate, a measure that does not take into account differences across settings in the proportion of women who wish to avoid getting pregnant, obscured the strength of the observed relationships. Further exploration of the factors underlying this relationship can inform policies to improve the quality of women’s lives.